Structural analysis of a stone arch bridge under incremental railway static loading - Rúben Silva (2019)
This paper reports on the modelling strategies used to represent the structural behaviour of a masonry single-arch railway bridge. The bridge structural behaviour is simulated by a 3D finite element model, in which the different bridge components are represented by homogeneous materials. The material nonlinear behaviour is simulated using a Drucker-Prager model. The assigned material properties are based on material testing, performed in similar stone masonry structures. The load-carrying capacity is evaluated using a 3D Ansys model and with a RING model of the bridge under incremental static loading representing normal railway traffic with appropriate configurations on the bridge deck, and the results compared.